Haemophilus influenzae Susceptibility Testing Within Four Hours by a Modification of the Autobac I System - Hosmer, Marion E. (1978)
By adding an XV strip to the eugonic broth or substituting Levinthal broth, the standard Autobac I susceptibility testing system may be used to determine susceptibility of Haemophilus influenzae to antimicrobial agents. Complete concordance was attained in testing 30 strains (5 resistant) by Autobac I, disk diffusion, and broth dilution methods. Autobac I results were available within 4 h after isolation of the organism.